Effect of novel superabsorbent polymer composites on the fresh and hardened properties of alkali-activated slag. (30th January 2020) - Fu, Chuanqing; Ye, Hailong; Lei, Aoke; Yang, Guojun; Wan, Pan
Highlights: Novel poly(sodium-acrylate acrylamide) superabsorbent polymer composites are synthesized. The impact of SAP composites on the fresh and hardened properties of AAS is evaluated. The micro silica and kaolin clay-reinforced SAP composites show better performance in AAS. Abstract: In this work, the poly(sodium-acrylate acrylamide) superabsorbent polymer (SAP) composites reinforced with micro silica and kaolin clay particles are evaluated as novel additives to control and improve the fresh and hardened properties of alkali-activated slag (AAS). The water swelling and retention capacity of plain and modified SAPs in various solutions pertinent to AAS binder systems (including deionized water, saturated Ca(OH)2, 1.0 M NaOH, 0.5 M Na2 CO3, and 0.5 M Na2 SO4 ) are studied using the gravimetric 'tea bag' and thermogravimetric methods, together with molecular analysis. The results show that the use of micro silica and kaolin clay-reinforced SAP composites slightly alleviates the negative influence of conventional SAP counterparts on the flowability, setting, and early-age compressive strength of AAS pastes. Nevertheless, the addition of SAP composites merely postpones the early-stage drying shrinkage development but tends to increase the long-term deformation of hardened AAS in unsealed conditions, likely due to the reduced bulk stiffness with enlarged porosity.